Sub-sensory vibratory noise augments the physiologic complexity of postural control in older adults. Issue 1 (December 2016) - Zhou, Junhong; Lipsitz, Lewis; Habtemariam, Daniel; Manor, Brad
Abstract Background Postural control requires numerous inputs interacting across multiple temporospatial scales. This organization, evidenced by the "complexity" contained within standing postural sway fluctuations, enables diverse system functionality. Age-related reduction of foot-sole somatosensation reduces standing postural sway complexity and diminishes the functionality of the postural control system. Sub-sensory vibrations applied to the foot soles reduce the speed and magnitude of sway and improve mobility in older adults. We thus hypothesized that these vibration-induced improvements to the functionality of the postural control system are associated with an increase in the standing postural sway complexity. Method Twelve healthy older adults aged 74 ± 8 years completed three visits to test the effects of foot sole vibrations at 0 % (i.e., no vibration), 70 and 85 % of the sensory threshold. Postural sway was assessed during eyes-open and eyes-closed standing. The complexity of sway time-series was quantified using multiscale entropy. The timed up-and-go (TUG) was completed to assess mobility. Results When standing without vibration, participants with lower foot sole vibratory thresholds (better sensation) had greater mediolateral (ML) sway complexity (r 2 = 0.49, p < 0.001), and those with greater ML sway complexity had faster TUG times (better mobility) (r 2 = 0.38, p < 0.001). Foot sole vibrations at 70 and 85 % of sensory threshold increased ML sway complexity during eyes-open and eyes-closed standing (p < 0.0001). Importantly, these vibration-induced increases in complexity correlated with improvements in the TUG test of mobility (r 2 = 0.15 0.42, p < 0.001 0.03). Conclusions Sub-sensory foot sole vibrations augment the postural control system functionality and such beneficial effects are reflected in an increase in the physiologic complexity of standing postural sway dynamics.